Misconception Profile of 11Th Grade High School Students on Membrane Transport Using Three Tier Diagnostic Tests - Tyas Tania Azqiya; Yuni Sri Rahayu (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
The learning method in Indonesia employed distance learning during the Covid-19 pandemic with the purpose that the Ministry of Education and Culture released a decree number 719/P/2020 on Diagnostic Assessment, of which one was meant to identify misconceptions with the intent that teachers must carry out. Identification of misconceptions needs to be done because it can interfere with the formation of concepts in the next material because there are several concepts that are correlated with other concepts. Cognitive assessment is one tool to recognize students that have misconceptions. The objective of this descriptive evaluative research is to assess the profile of students’ misconceptions and the factors that have contributed to misconceptions faced by students in membrane transport sub materials using the Three Tier Diagnostic Test, and justification of some concepts at the highest misconceptions. The research phase consisted of validation of the test instrument, testing the student using the test instrument, analyzing the outcomes of the sample using a table for grouping students’ conceptions and parameters for deciding the level of misconceptions, and drawing the conclusions. The target of this research is 40 students of State High School 1 Babat in 11th grade that was XI Science 1 and XI Science 2 classes. The findings revealed that the misconception profile of students who understand the concept, do not understand the concept, and have encountered misconceptions were 9.625%; 31.250%; and 59.125% respectively. Students who experienced misconceptions were divided into three criteria for the level of misconception, a namely high misconception by 45.00%, a moderate misconception by 37.50%, and low misconception by 17.50%. Factors that affect the misconceptions faced by students were teacher, teaching method, learning media, students’ textbooks, and including students themselves. This research implies that students experience more misconceptions than understand the concepts. Keywords: Membrane Transport, Misconception Profile, Three Tier Diagnostic Test